Peran Strategis Tenaga Kesehatan dalam Penyuluhan dan Pencegahan Penyakit Menular pada Fase Tanggap Darurat Bencana - Ficky Adi Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2026)
Indonesia, as a country with a high level of disaster vulnerability, faces an increased risk of communicable diseases during the emergency response phase due to disrupted sanitation, limited access to clean water, overcrowded evacuation shelters, and weakened health services. This study aims to analyze the strategic role of health workers in health education and the prevention of communicable diseases during disaster emergency response. The method used is a literature review of relevant national and international scientific articles. The findings indicate that health workers have a multidimensional role, not only as providers of curative services but also as educators, change agents, advocates, and collaborators in promotive and preventive efforts. Effective health education, participatory risk communication, strengthened epidemiological surveillance, and the implementation of Infection Prevention and Control (IPC) are key strategies to reduce the risk of communicable disease outbreaks. However, implementation in the field still faces challenges, including limited resources, cross-sectoral coordination constraints, heavy workloads, and suboptimal disaster-related policy systems and standard operating procedures (SOPs). Therefore, strengthening the capacity of health workers through training, policy support, and community-based approaches is necessary to enhance health system resilience in responding to disaster crises.